Receptors for EGF and oestradiol and thymidinekinase activity in different histological subgroups of human mammary carcinomas. - Skoog, L. (Nature Publishing Group, 1986)
The cellular content of receptors for epidermal growth factor (EGF) was measured in different histological subgroups of human mammary carcinomas. EGF receptors were detected in 36% of the ductal and all the medullary carcinomas. In contrast lobular and pure colloid tumours did not contain measurable amounts of the receptor. The receptor was found both among tumours with an euploid and aneuploid DNA pattern. The EGF receptor is thus found in carcinomas with a varying degree of differentiation as judged by the cellular DNA pattern. There was no correlation between the proliferative activity of the tumours as measured by thymidinekinase activity and the amount of EGF receptors in the tumour. Tumours with detectable EGF receptor often had low levels of oestrogen receptor. This finding could only partly be explained by the menstrual status of the patients.